Salt stress enhances bioactive compound accumulation in Glycyrrhiza inflata: integrated transcriptomics and physiological analysis reveals germplasm-specific adaptation mechanisms - Zhu, Bo; Cheng, LinYuan; Shi, Nana; Chen, Pizheng; Guo, Fei; Qu, Yiyuan; Yao, Hua; Shen, Haitao (Frontiers in Plant Science, 2025)
IntroductionGlycyrrhiza inflata Batal., a halophytic plant predominantly found in the saline-alkali deserts of southern Xinjiang, China, is renowned for its abundance of bioactive compounds like flavonoids and triterpenoids. It demonstrates considerable potential for applications within the pharmaceutical, food, health product, and cosmetic industries. Additionally, its cultivation presents the dual advantage of generating economic returns and facilitating the remediation of saline-alkali soils.MethodsThis study examined 29 distinct provenances of G. inflata collected from various locations across Xinjiang. Key agronomic traits and the content of bioactive compounds in the underground parts of one-year-old plants grown in severely saline-alkali soil were measured to assess inter-germplasm variation. Subsequently, four germplasms displaying contrasting quality and salt tolerance were selected for controlled salt stress treatment (150 mM NaCl) under laboratory conditions. The effects on seed germination, root bioactive compound content, endogenous hormone levels, and key physiological and biochemical indices were analyzed. An integrated analysis of salt stress transcriptomic data was conducted using Weighted Gene Co-expression Network Analysis (WGCNA). This involved expression clustering and enrichment analysis of differentially expressed genes (DEGs) to investigate the impact of salt stress on genes related to bioactive compound biosynthesis (particularly flavonoids), endogenous hormone pathways, and key flavonoid biosynthesis enzymes.ResultsThe findings indicate that germplasms with superior stress tolerance maintained higher and more stable levels of antioxidant enzymes. In response to stress, these resilient germplasms modulated hormone signaling, notably upregulating abscisic acid (ABA) and downregulating auxin (IAA), thereby reallocating resources towards defense mechanisms. Crucially, salt stress was identified as an effective means to enhance the accumulation of bioactive compounds in G. inflata. Transcriptomic analysis revealed substantial divergence in post-stress gene expression patterns among germplasms, implicating key pathways such as plant hormone signal transduction, flavonoid biosynthesis, and phenylpropanoid metabolism.DiscussionThis research establishes a foundation for breeding high-quality G. inflata germplasms adapted to desert saline-alkali environments and provides valuable insights into the molecular mechanisms regulating the synthesis and accumulation of its valuable bioactive compounds.